HUMOROUS IRONY IN SPONTANEOUS SPEECH: FROM THE FLOUTING OF EXPECTATIONS TO NON-SERIOUSNESS - Krajnc Ivič, Mira; Mihailović, Larisa (Slavia Centralis, 2026)
The paper examines humorous irony in spontaneous speech based on a corpus-based analysis of the Krohot (Corpus of Conversational Humor in the Slovene Language) 1.0 data. Irony is conceptualized as a context-dependent, metarepresentational form of indirect expression in which the listener reconstructs the speaker’s implicit stance based on a contrast between what is said and what is expected. Irony becomes humorous when this contrast triggers a playful shift into non-seriousness and enables a tension-relieving resolution of incongruity. The quantitative-qualitative analysis shows that humorous irony most frequently co-occurs with the combination of the corpus annotations ‘vocabulary’ and ‘attitude’. In the former, humorousness arises from word choice while in the latter it comes from the speaker’s attitude toward the content.